Anatomical and Visual Outcomes after LASIK Performed in Myopic Eyes with the WaveLight® Refractive Suite (Alcon® Laboratories Inc., USA) - Imene Salah-Mabed; Sarah Moran; Emmanuelle Perez; Guillaume Debellemanière; Damien Gatinel (Journal of Ophthalmology)
Purpose. To evaluate changes in corneal anatomy and quality of vision following LASIK refractive surgery for mild to high myopia using the WaveLight® Refractive Suite (Alcon® Laboratories Inc., USA). Setting. Rothschild Foundation, Paris, France. Design. Prospective interventional case series. Methods. We examined 60 myopic eyes (average SE −4.5 D, from −9.3 to −0.75 D) of 30 patients from 21.3 to 38.7 years old. Pachymetry, keratometry, Q factor, corneal aberrations, visual acuity (VA), contrast sensitivity, dry eye assessment, and quality of vision were measured preoperatively, one day (D1), and 1, 3, and 6 months postoperatively. Results. 6 months postoperatively, keratometry became flatter, and the Q factor became more oblate (from −0.18 ± 0.08 to +0.19 ± 0.06). Pachymetry decreased by 117.9 ± 62.2 µm at D1 and increased by 37.87 ± 32.6 µm between D1 and M6. Refraction was emmetropic at D1 and remained stable thereafter. Six months after surgery, VA was slightly but nonsignificantly improved (<0.05 log MAR), whereas contrast sensitivity remained unchanged. Quality of vision was not affected by surgery and was more related to dry eye symptoms than to corneal HOAs (r2 = 0.49; p<0.001 vs. r2 = 0.03; p<0.001). Conclusions. LASIK surgery for moderate to high myopia, performed with the WaveLight® Refractive Suite, showed good postoperative outcomes, with demonstrated safety, predictability, efficiency, and stability. This is probably due to well-controlled spherical aberration and the use of large optical zones. Besides, we can assume that the patients’ quality of vision depends more on the postoperative dry eye disease generated by the laser than on the induced HOAs.